Metacognitive Awareness Based on Gender in Conceptual Change Learning Assisted Android Mobile-learning on the Topic of the Human Reproductive System - Wiono, Wisnu Juli; Dewi, Safira Permata (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
Abstract: Metacognitive Awareness Based on Gender in Conceptual Change Learning Assisted Android Mobile-learning on the Topic of the Human Reproductive System. This study aims to describe the level of metacognitive awareness of male and female students in conceptual change learning on the topic of the human reproductive system, the relationship between knowledge about cognition and cognitive regulation. The research subjects were students of class XI at a high school in Bandar Lampung. The instrument used to collect data is a metacognitive awareness questionnaire developed by Schraw & Dennison (1996). The results of the study show that male and female students are dominantly at the level of "developing" metacognitive awareness in the sense that they can be helped towards awareness of thinking for themselves if they are inspired or supported. This study also revealed that girls are more dominant in their minds-on, while male students tend to be more hands-on. Each knowledge about cognition and regulation of cognition has a strong relationship, both in male and female students. Through this research, it appears that conceptual change learning facilitates male and female students to identify and revise concepts that develop in society related to the human reproductive system to become scientifically correct. DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27135